Analisis Pengaruh Arus Kas dan Pertumbuhan Laba Terhadap Return Saham Pada Perusahaan Manufaktur Sektor Industri Dasar Dan kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2011 - 2014 - Zaki Muhammad; Medya Destalita (SOSIALITA, 2017)
This research aims to analyze the effect cash flow of operating, cash flow of investment, cash flow of financial and profit growth on stock returns in basic and chemical industry manufacturing companies listed on the Indonesia Stock Exchange. The sample of this research consists of 11 companies manufacturing basic and chemical industry sectors listed in Indonesia Stock Exchange 2011-2014 which is determined through purposive sampling. This research uses multiple regression analysis model of data panel. The result of the research shows that the growth of earnings partially significant effect on stock return, while cash flow of operating, cash flow of investment, and cash flow of financial partially have no significant effect on stock return. F test results show that cash flow of operating, cash flow of investment, cash flow of financial, and profit growth simultaneously have no significant effect on stock returns.